In Silico Analysis of Non-Conventional Oxidative Stress-Related Enzymes and Their Potential Relationship with Carcinogenesis - Seiva, Fábio Rodrigues Ferreira [UNESP]; Agneis, Maria Luisa Gonçalves [UNESP]; de Almeida, Matheus Ribas [UNESP]; Caputo, Wesley Ladeira [UNESP]; de Souza, Milena Cremer; das Neves, Karoliny Alves [UNESP]; Oliveira, Érika Novais [UNESP]; Justulin, Luis Antônio [UNESP]; Chuffa, Luiz Gustavo de Almeida [UNESP] (MDPI, 2024)
Carcinogenesis is driven by complex molecular events, often involving key enzymes that regulate oxidative stress (OS). While classical enzymes such as SOD, catalase, and GPx have been extensively studied, other, non-classical oxidative stress-related enzymes (OSRE) may play critical roles in cancer progression. We aimed to explore the role of OSRE involved in an OS scenario and to assess their potential contribution to carcinogenesis in some of the most prevalent cancer types. Through data mining and bioinformatic analysis of gene and protein expression and mutation data, we identified OSRE with altered expression and mutations across cancer types. Functional pathways involving EGFR, MT-ND, GST, PLCG2, PRDX6, SRC, and JAK2 were investigated. Our findings reveal that enzymes traditionally considered peripheral to OS play significant roles in tumor progression. Those OSRE may contribute to cancer initiation and progression, as well as be involved with cancer hallmarks, such as EMT and invasion, proliferation, and ROS production. In addition, enzymes like SRC and JAK2 were found to have dual roles in both promoting ROS generation and being modulated by OS. OSRE also interact with key oncogenic signaling pathways, including Wnt/β-catenin and JAK2/STAT3, linking them to cancer aggressiveness and therapeutic resistance. Future research should focus on translating these findings into clinical applications, including the development of novel inhibitors or drugs targeting these non-classical enzymes.
Keywords: bioinformatic; cancer; enzymatic system; in silico analysis; tumor biology